Physical Characteristics of Lip Cream Preparations with Natural Coloring Beetroot Extract (Beta Vulgaris L.) - Fazadini, Safira Yulita; Ernawati, Iin (Universitas Muhammadiyah Lamongan, 2024)
Introduction: Cosmetics are a primary need for women to help them appear more attractive, one of the lip coloring cosmetics that is currently in great demand among consumers is lip cream. Lip cream is a liquid lipstick preparation that can moisturize the lips for a long time compared to solid form and produces a more even color on the lips. Lip cream coloring ingredients can be obtained from synthetic dyes and natural dyes. The coloring (pigment) found in red beets is betalain which can be used as an antioxidantMethods: The research method is experimental. This research was carried out to formulate beetroot (Beta vulgaris L.) extract as a natural coloring for lip cream preparations. The independent variable in this research is beetroot (Beta vulgaris L.) extract as a natural coloring and the dependent variable is the physical characteristics of lip cream including organoleptic (shape, color and odor), pH, homogeneity and spread ability. Data analysis is descriptive.Results: The results of this research show that the lip cream preparation has the characteristics of being in a semi-solid form, with a purplish red color, and a distinctive rose smell. The color and smell did not change until day 7. The pH test showed a pH of 3.39 on day 1 and 5.49 on day 7. The homogeneity test showed it was homogeneous until day 7. The spreadability test showed that it could be spread with an average spreadability of 5 cm.Conclusion: This research shows that the lip cream color is dark or thick red in the preparation, organoleptic test, pH test, spreadability is in accordance with the desired design.